2017
DOI: 10.1007/s00262-017-1995-x
|View full text |Cite
|
Sign up to set email alerts
|

IDO and galectin-3 hamper the ex vivo generation of clinical grade tumor-specific T cells for adoptive cell therapy in metastatic melanoma

Abstract: Adoptive T cell transfer (ACT) with ex vivo-expanded tumor-reactive T cells proved to be successful for the treatment of metastatic melanoma patients. Mixed lymphocyte tumor cell cultures (MLTC) can be used to generate tumor-specific T cells for ACT; however, in a number of cases tumor-reactive T cell, expansion is far from optimal. We hypothesized that this is due to tumor intrinsic and extrinsic factors and aimed to identify and manipulate these factors so to optimize our clinical, GMP-compliant MLTC protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…In one experiment, extracellular Gal-3 had a suppressive effect on CD8 T cells as a Gal-3-deficient melanoma tumor cell line or its supernatant cultured with tumor-reactive CD8 T cells induced a significant expansion and increase in IFN-γ levels in the CD8 T cells compared to co-cultures with Gal-3-expressing tumor cell lines or supernatant. 22 , 23 In human tumor-derived CD8 T cells, Gal-3 expression has been associated with the loss of TCR and CD8 marker localization at the immunological synapse and subsequent loss of effector function. 24 , 25 A recent study showed that extracellular Gal-3 binds to lymphocyte activation gene 3 (LAG-3) on CD8 T cells and possibly suppresses CD8 T cell function.…”
Section: Galectin-3 In Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one experiment, extracellular Gal-3 had a suppressive effect on CD8 T cells as a Gal-3-deficient melanoma tumor cell line or its supernatant cultured with tumor-reactive CD8 T cells induced a significant expansion and increase in IFN-γ levels in the CD8 T cells compared to co-cultures with Gal-3-expressing tumor cell lines or supernatant. 22 , 23 In human tumor-derived CD8 T cells, Gal-3 expression has been associated with the loss of TCR and CD8 marker localization at the immunological synapse and subsequent loss of effector function. 24 , 25 A recent study showed that extracellular Gal-3 binds to lymphocyte activation gene 3 (LAG-3) on CD8 T cells and possibly suppresses CD8 T cell function.…”
Section: Galectin-3 In Immune Cellsmentioning
confidence: 99%
“…Gal-3 plays a crucial role in promoting tumor-driven immune suppression. In mixed lymphocyte cultures of T cells derived from peripheral blood mixed with autologous tumor cells, inhibition of tumor-expressed Gal-3 led to the expansion of high numbers of tumor-reactive T cells, 22 suggesting that Gal-3 suppresses expansion of tumor-reactive T cells. Furthermore, Gal-3 secreted by tumor cells has been shown to alter macrophage polarization from M1 (anti-tumor macrophage) to M2 (pro-tumor macrophage), trigger CD8 T cell apoptosis, and restrict T cell receptor (TCR) clustering, all of which contribute to immunosuppression and facilitate tumor escape ( Fig.…”
Section: Galectin-3 Contribution To Immunosuppressionmentioning
confidence: 99%
“…This complex molecular structure reduces IFNγ diffusion through the tumor matrix and the chemokine gradient that is necessary to favor T lymphocytes migration into the tumor [21]. The finding that experimental transfer of cytotoxic T lymphocytes in vivo reduces tumor growth only after galectin-3 inactivation further support the key role of galectin-3 in favoring tumor immune escape [23]. This scenario opens the possibility that a tumor-specific “galectin signature” could be a surrogate predictive marker of tumor responsiveness to checkpoint inhibitors-based immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, treatment with a small molecule inhibitor targeting Gal3 (GB1107) boosts anti-PD-L1 therapy in lung adenocarcinoma preclinical assays by promoting CD8+ T-cell infiltration and M1 macrophage polarization [116]. In melanomas, ex vivo expansion of T-cells for adoptive cell transfer therapy was directly related to the amount of Gal3 secreted by tumor cells and blocking the lectin enhanced T-cell activation [117].…”
Section: Clinical Opportunitiesmentioning
confidence: 99%